Argumentation of Criminal Liability Law for Commercial Sex Workers (PSK) - Alvian Dwiangga Wijaya; Indawati, S.H., M.Kn., Yana (Fakultas Hukum Universitas Widya Mataram, 2023)
One that is still a trend or problem in this country is prostitution. Prostitution is a crime that should be processed to its roots, because prostitution is also a structural problem that is fundamental and often found in society because to this day it is still a crime. moral problem. UU no. 12 of 2022 concerning Crimes of Sexual Violence is the hope for all groups so that their rights can be protected, especially for women and children who are often victims of the circulation of the prostitution business. This type of research used by the author is normative research. This normative research is a type of legal research that originates from a scientific research procedure whose aim is to find the truth based on legal objectives from a normative perspective. Article 12 of Law No. 12 of 2022 concerning Crimes of Sexual Violence has apparently not been able to ensnare PSK because there is no provision that regulates that the actions committed by PSK violate the provisions of the criminal law. Keywords: Commercial Sex Workers (Psk), Prostitution, Law No.12 concerning Crimes of Sexual Violence